EXTROVERT STUDENTS BY MALE AND FEMALE ON THE STUDENTS' SPEAKING ABILITY - Putri Mirza Hijazi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This research is aimed to find the comparison of students’ speaking ability between male and female in second semester of University of Islam Malang. The specific of this research were to find out whether there is a significant difference between male and female students’ speaking skill in second semester of English Department in University of Islam Malang. The population of this study were 48 students and the sample were 33 students; 15 male students and 18 female students. In collecting the data, the researcher used speaking test and the topic was describing someone. To determine the comparison between two variables researched, the researcher used independent sample t-test formula and analysed by using SPSS version 20.0. The findings showed that the Sig. (2-tailed) is .974. it can be concluded the Sig. (2-tailed) ≥ .05. It means that null hypothesis (H0) is accepted, therefore the alternative hypothesis (H1) is rejected. in conclusion, there is no significant difference between male and female students’ speaking ability in second semester of University of Islam Malang although the result of mean score of female students was higher than male students, even it is only slightly different. Key words: Speaking ability, Extrovert personality